Review of 100 cases of single port laparoscopic cholecystectomy - Eun Jung Koo; Soon Hwa Youn; Yang Hyun Baek; Young Hoon Roh; Hong Jo Choi; Young Hoon Kim; Ghap Joong Jung (Annals of surgical treatment and research, 2012)
Purpose: Single port laparoscopic cholecystectomy (SPLC) is a new advanced technique in laparoscopic surgery. Many laparoscopic surgeons seek to gain skill in this new technique. However, little data has been accumulated and published formally yet. This article reports the achievement of 100 cases of SPLC with the hopes it will encourage laparoscopic surgery centers in the early adoption of SPLC. Methods: A retrospective review of 100 prospectively selected cases of SPLC was carried out. All patients had received elective SPLC by a single surgeon in our center from May 2009 to December 2010. Our review suggests patients' character, perioperative data and postoperative outcomes. Results: Forty-two men and 58 women with an average age of 45.8 years had received SPLC. Their mean body mass index (BMI) was 23.85 kg/m2. The mean operating time took 76.75 minutes. However, operating time was decreased according to the increase of experience of SPLC cases. Twenty-one cases were converted to multi-port surgery. BMI, age, previous low abdominal surgical history did not seem to affect conversion to multi-port surgery. No cases were converted to open surgery. Mean duration of hospital stay was 2.18 days. Six patients had experienced complications from which they had recovered after conservative treatment. Conclusion: SPLC is a safe and practicable technique. The operating time is moderate and can be reduced with the surgeon's experience. At first, strict criteria was indicated for SPLC, however, with surgical experience, the criteria and area of SPLC can be broadened. SPLC is occupying a greater domain of conventional laparoscopic cholecystectomy KCI Citation Count: 13